2011
DOI: 10.1128/jcm.00231-11
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Moxifloxacin Resistance in Clinical Mycobacterium tuberculosis Isolates in Houston, Texas

Abstract: Comprehensive data on the prevalence of quinolone resistance in Mycobacterium tuberculosis clinical isolates in the United States are scarce. By use of a systematic population-based approach, M. tuberculosis strains from tuberculosis (TB) cases were collected in Harris County, TX, in 2007 to 2008. The susceptibilities of M. tuberculosis isolates to moxifloxacin and ofloxacin were determined by the agar proportion indirect susceptibility method. Spoligotyping and 12-locus mycobacterial interspersed repetitive u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
(35 reference statements)
1
6
1
Order By: Relevance
“…The variability might also be due to selection bias, since the vast majority of studies were made retrospectively. Regarding the substitutions in GyrA, those at position D94 were the most frequent, followed by A90V and S91P (Table 4), as previously reported (11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The variability might also be due to selection bias, since the vast majority of studies were made retrospectively. Regarding the substitutions in GyrA, those at position D94 were the most frequent, followed by A90V and S91P (Table 4), as previously reported (11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 60%
“…The second major result of our study is that FQ r isolates harbored more substitutions in GyrA or GyrB than is generally reported in the literature (93% versus an average of 81% in the 13 studies providing both gyrA and gyrB sequence data; P ϭ 0.02) ( Tables 2 and 4) (11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Among these substitutions found in the FQ r isolates, we observed a higher proportion in GyrB than was previously published (11.5% versus an average of 3%) (11).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…There were 11 studies from 10 countries identified by our search strategy that were included in this review, including this current surveillance study (Table 1). 11,13,[27][28][29][30][31][32][33][34] The studies were carried out between 1995 and 2013. Study populations were diverse, including TB patients from field clinics, hospitals, and our study which included all TB patients from a country state.…”
Section: The Global Burden Of Fluoroquinolone Resistancementioning
confidence: 99%
“…Due to its wide distribution pattern, can easily invade to an intracellular compartment of Mycobacterium and produce strong effects like macrophages without cross-resistance to antitubercular drugs [26][27][28]. Among them, moxifloxacin resistance to MDR-TB is very low [29] and highly effective to isoniazide and rifampicin resistance cases. The main targets of its bactericidal actions to DNA gyrase and topoisomerase IV [30].…”
Section: Citationmentioning
confidence: 99%